Difference of coagulation features between severe pneumonia induced by SARS-CoV2 and non-SARS-CoV2 - Yin, Shiyu; Huang, Ming; Li, Dengju; Tang, Ning (Journal of thrombosis and thrombolysis, 2021)
Severe coronavirus disease 2019 (COVID-19) is commonly complicated with coagulopathy, the difference of coagulation features between severe pneumonia induced by SARS-CoV2 and non-SARS-CoV2 has not been analyzed. Coagulation results and clinical features of consecutive patients with severe pneumonia induced by SARS-CoV2 (COVID group) and non-SARS-CoV2 (non-COVID group) in Tongji hospital were retrospectively analyzed and compared. Whether patients with elevated D-dimer could benefit from anticoagulant treatment was evaluated. There were 449 COVID patients and 104 non-COVID patients enrolled into the study. The 28-day mortality in COVID group was approximately twofold of mortality in non-COVID group (29.8% vs. 15.4%, P = 0.003), COVID group were older (65.1 ± 12.0 vs. 58.4 ± 18.0, years, P < 0.001) and with higher platelet count (215 ± 100 vs. 188 ± 98, ×10 9 /L, P = 0.015), comparing to non-COVID group. The 28-day mortality of heparin users were lower than nonusers In COVID group with D-dimer > 3.0 μg/mL (32.8% vs. 52.4%, P = 0.017). Patients with severe pneumonia induced by SARS-CoV2 had higher platelet count than those induced by non-SARS-CoV2, and only the former with markedly elevated D-dimer may benefit from anticoagulant treatment.